WH-Questions in Japanese and Speech Act Phrase - Oguro, Takeshi (Linguistica Atlantica, 2016)
This paper examines several types of WH-questions in Japanese and their interaction with Speech Act Phrase, which is a projection hosting discourse participants (the speaker and the hearer) argued for by scholars such as Speas & Tenny (2003) and Haegeman & Hill (2013). Miyagawa (2012) analyzes Japanese WH-questions in terms of Speech Act Phrase, suggesting that the obligatory presence of the politeness marker in matrix WH-questions means that the hearer plays an important role. Yokoyama (2013) provides grammatical matrix WH-questions lacking the politeness marker such as conjectural questions and rhetorical questions. I argue that Yokoyama’s examples are not damaging evidence for Miyagawa’s approach but they constitute supporting evidence for it by showing that in these questions it is the speaker, which is also a discourse participant, that plays an important role. I also suggest a slight modification of typology of WH-questions offered by Littell, Mathewson & Peterson (2010), which reveals a type of WH-questions, namely quizmaster questions, whose behavior also supports Miyagawa’s analysis.